Databáze bodů zájmu bezbariérovosti - Sedlák, Pavel; Šimonová, Stanislava; Komárková, Jitka; Rajšner, Ivo; Pošvová, Kristýna (Univerzita Pardubice, 2010)
The aim of the paper is to show the way how design data model database of points of interest for physically impaired people. The database design is based on the principles of data modeling and its implementation is planned in ArcGIS Desktop environment. The work is also studying the possibility of converting some of the proposed database data formats for the use of points of interest in various GPS devices.
Keywords: geodatabase; barriers; arcgis desktop; CASE tools; UML